2018
DOI: 10.1155/2018/3235950
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Qigong Wuqinxi in the Improvement of Health Condition, Prevention, and Treatment of Chronic Diseases: Evidence from a Systematic Review

Abstract: Purpose Qigong is a modality of traditional Chinese mind-body medicine that has been used to prevent and cure ailments, to improve health in China for thousands of years. Wuqinxi, a Chinese traditional Qigong that focuses on mind-body integration, is thought to be an effective exercise in promoting physical and mental wellbeing. Thus, we summarized the evidence and aim to unravel effects of Wuqinxi on health outcomes. Methods We performed a systematic review of Wuqinxi studies published in English or Chinese s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 18 publications
(37 reference statements)
1
35
0
3
Order By: Relevance
“…Wuqinxi is one traditional Chinese exercise that is starting to receive attention in the research literature (e.g., Tai Chi, Buduanjin, and other Qigong forms) [10,11]. The Wuqinxi exercise routine was originally choreographed by an ancient Chinese physician in the Donghan Dynasty [12]; it is figuratively known as the “five animals” exercise, including movements imitating tigers, deer, bears, apes, and birds [12]. Wuqinxi modalities such as Tai Chi [13,14,15], Baduanjin [16,17,18], and Yoga [19,20,21] also involve symmetrically slow movements, integrated with breathing techniques, physical and mental relaxation, body awareness, and meditation.…”
Section: Introductionmentioning
confidence: 99%
“…Wuqinxi is one traditional Chinese exercise that is starting to receive attention in the research literature (e.g., Tai Chi, Buduanjin, and other Qigong forms) [10,11]. The Wuqinxi exercise routine was originally choreographed by an ancient Chinese physician in the Donghan Dynasty [12]; it is figuratively known as the “five animals” exercise, including movements imitating tigers, deer, bears, apes, and birds [12]. Wuqinxi modalities such as Tai Chi [13,14,15], Baduanjin [16,17,18], and Yoga [19,20,21] also involve symmetrically slow movements, integrated with breathing techniques, physical and mental relaxation, body awareness, and meditation.…”
Section: Introductionmentioning
confidence: 99%
“…Wu Qin Xi is an integrated qigong exercise system that consists of movements that imitate the technical actions and breathing of five animals (tiger, deer, bear, monkey, and crane) while attending to unification of the regulation of one's body, respiration, and mind ( 17 ). It incorporates movement of all body joints and stretching of the upper and lower limbs and is thus considered to be an effective mind–body rehabilitative intervention for elderly individuals ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…erefore, compared with Tai-chi exercise, Wuqinxi pays more attention to the relationship between human and nature. With the enhancement of people's awareness of self-care, more and more studies have shown the benefits of Wuqinxi in improving health and treating chronic diseases [17][18][19]. A prospective study demonstrated that Wuqinxi can improve the function of the lumbosacral multifidus and reduce LBP, but no further efficacy evaluation was carried out [20].…”
Section: Introductionmentioning
confidence: 99%